Analisis Kekasaran Permukaan Benda Kerja Terhadap Pemakanan Kering dan Basah Terhadap Material Baja AISI 1045 Pada Proses Pemesinan CNC Bubut - Verdian, Muhammad; Oktriadi, Yudi (Jurnal Inovasi Teknologi Terapan, 2023)
Times are growing rapidly. One of them is marked by the development of technology that facilitates human work, for example CNC lathes. In the machining process, a CNC lathe produces a surface roughness value. The smaller the surface roughness value, the better. The tool for measuring surface roughness is the Surface Roughness Tester. The purpose of this study was to obtain the surface roughness value of the dry and wet feed machining processes or by using a cooling medium and not using a cooling medium, namely drromus, which then obtained the best results from the two feeding processes. The method used is the Taguchi method developed by Genichi Taguchi where this method is used to improve the quality of production results from the manufacturing process. The results of the surface roughness research obtained for wet food from 3 repetitions on average were 2.068, 1.233, 1.621 and 1.253. And the yield values for dry food processing are 1.670, 0.987, 1.146 and 1.679. The conclusion obtained is that the smallest roughness value in the wet feeding process is 1.233 with parameters RPM 1273.88, Deft Of Cut 1mm, and Feeding 0.16 mm/put. And for dry feeding it is 0.987 with parameters RPM 1273.88, Deft Of Cut 1mm, and Feeding 0.16 mm/put.